2013
DOI: 10.3732/ajb.1200482
|View full text |Cite
|
Sign up to set email alerts
|

Geographic differences in patterns of genetic differentiation among bitter and sweet manioc (Manihot esculenta subsp. esculenta; Euphorbiaceae)

Abstract: Lack of differentiation in Africa is most likely due to postintroduction hybridization between bitter and sweet manioc. Inconsistent transfer from South America to Africa of ethnobotanical knowledge surrounding use-category management may contribute to increased hybridization in Africa. Investigating this issue requires more data on the variation in cyanogenesis in roots within and among manioc populations and how manioc diversity is managed on the farm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 51 publications
4
27
0
Order By: Relevance
“…Based on the pattern of dispersion in PCoA of the groups identified by Structure and of the 188 varieties characterized by the levels of cyanogenic glycosides using available passport data, we found weak sweet-bitter structure, although errors in the passport identification, partial chemical characterization of manioc accessions and mixture during clonal multiplication (on farm and ex situ) may contribute to this. Bradbury et al (2013) also showed, in African varieties, the occurrence of hybridization, incorrect passport data, and misidentification of sweet or bitter varieties by farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the pattern of dispersion in PCoA of the groups identified by Structure and of the 188 varieties characterized by the levels of cyanogenic glycosides using available passport data, we found weak sweet-bitter structure, although errors in the passport identification, partial chemical characterization of manioc accessions and mixture during clonal multiplication (on farm and ex situ) may contribute to this. Bradbury et al (2013) also showed, in African varieties, the occurrence of hybridization, incorrect passport data, and misidentification of sweet or bitter varieties by farmers.…”
Section: Discussionmentioning
confidence: 99%
“…; Bradbury et al. ). Konzo is the irreversible upper motor neuron damage caused by consumption of high dietary cyanogens especially from insufficiently processed cassava roots.…”
Section: Introductionmentioning
confidence: 99%
“…They also harvest 'sweet' cassavas earlier than 'bitter' types, in order to avoid formation of fibers, due to root lignification. Maybe this different type of selection, and the separation that farmers promote in their farms have contributed to generate a slight genetic differentiation detected by molecular markers in South America (Mühlen et al 2000, Elias et al 2004, Alves-Pereira et al 2011, Bradbury et al 2013), which did not occur in Africa (Bradbury et al 2013). Due to these differences in usage, 'sweet' and 'bitter' cassava genetic breeding programs are specific for each type (Fukuda et al 2002, Ceballos et al 2004).…”
Section: Introductionmentioning
confidence: 99%